Sustainable sanitation from a multi-layered approach: the case of Costa Rica - Cindy (Población y Salud en Mesoamérica)
The purpose of this article is to present the case of Costa Rica in its recent efforts to achieve sustainable environmental sanitation. Mainly, it is based on a theoretical framework that integrates the notion of environmental sanitation practices at multiple levels: the macro level (environmental and social policies), and at the micro level (community actions and individual daily practices). The context of Costa Rica is taken into account, since it presents an interesting case study in terms of environmental sanitation. On the one hand, it is a country widely recognized for its ecological policies framed within a "green agenda", with high social development indexes. However; on the other hand, it faces increasingly greater challenges in terms of sanitation planning, inter-institutional coordination, legislation, financing and maintenance of current sanitation systems. This article takes up some results of the author's doctorate study, which conducted a mixed-methods approach. The qualitative data were obtained from in-depth interviews with national authorities, locals, community leaders, and heads of households. The quantitative data were obtained from the application of a survey in three different communities with rural, urban, and semi-urban characteristics. At the national level, the main result is a paradigm shift in the conception of health, where the joint production of healthy environments should be paramount, within the framework of the right to live in a healthy and sustainable environment. At the community level, local efforts to protect their natural resources for tourism or productive purposes are highlighted, and at the individual level a mixture of reactive and proactive daily practices is found.